Estudios sobre la estabilidad del virus del rayado fino del maíz por degradación enzimática del ARN viral y microscopia electrónica de las partículas - Pereira Reyes, Reinaldo (1986)
The stability of "Maize Rayado Fino Virus" capsids was studied correlating enzymatic degradation analysis of the RNA in full capsids with electron microscopy of negatively stained particles. The great thermal stability of pancreatic ribonuclease A, combined with the strong change in absorbance of the nucleic acids upon hydrolisis, provide a convenient assay for RNA release, which correlates with quantitative observations of the particles in the electron microscope. A repeatable transition between 75° and 80°C is observed with MRFV, presumably due to cooperative opening of the closed shell, followed by the release of the encapsidated RNA.